Revealing a new species of Agarista (Ericaceae) endemic to the Chapada Diamantina, Brazil, segregated from A. revoluta by multiple evidence - Sampaio, Ariadne A.; Romão, Gerson O.; Dorea, Marcos C.; Oliveira, Reyjane P. (Phytotaxa, 2023)
Agarista is a genus belonging to the family Ericaceae that includes ca. 32 species. It occurs predominantly in South America, mainly in Brazil, where 21 species have been documented. During our floristic and taxonomic studies of Ericaceae from the state of Bahia, in northeastern Brazil, we found specimens from the Chapada Diamantina region identified in herbaria as Agarista aff. revoluta. Those samples were clearly distinct from A. revoluta by the greater length and width of the leaves, and the absence of indument on the rachis, flowers, and leaves, as well as leaf anatomy features. Thus, we recognize these as separate taxonomic entities and the new species is herein described as A. revolutissima, which is endemic to the campo rupestre of Morro do Chapéu municipality, while A. revoluta occurs along the Atlantic Forest, being known from the restinga and humid forests.